The most applicable recruitment and selection process for DBL Pharmaceuticals Ltd. as a new organization in a pharmaceutical industry - Amin, Atia (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.